Site of transcription of ribosomal RNA and intranucleolar structure in HeLa cells. - Hozák, P; Cook, P; Schöfer, C; Mosgöller, W; Wachtler, F (1994)
Sites of transcription of ribosomal RNA in HeLa cells were visualized by electron microscopy. Cells were either incubated with Br-uridine, or permeabilized and then incubated with BrUTP, before sites containing Br-RNA were immunolabeled with gold particles. Short incubations ensured that most incorporated analogue remained at synthetic sites. Fibrillar centres were unlabelled except at their periphery; label was concentrated over certain regions of the surrounding dense fibrillar component. These results suggest that the dense fibrillar component is the site of rRNA transcription. After dispersing the granular component and the dense fibrillar component by a hypotonic treatment, removal of most chromatin and preparation of resinless sections, fibrillar centres remained fixed to a nucleoskeleton. These structural and functional features are incorporated into a model for rRNA transcription.